Методы термодинамики, тепло- и массопереноса для решения обратной задачи внутренней баллистики - Анипко, О. Б.; Бирюков, И. Ю. (НТУ "ХПИ", 2005)
The article deals with the approach suggested for determination of projectile ballistic characteristics at different stages of their usage on the data basis of experimental researches and the reverse task of inner ballistic
Keywords: порох пироксилиновый; пороховые элементы; старение порохов; молекулярная диффузия; нитроклетчатка; пороховой заряд